2013
DOI: 10.1039/c3ra43090a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and binding of proflavine diazides as functional intercalators for directed assembly on DNA

Abstract: Proflavine diazide (PD) with amido-azide substituents on the amine groups and its N-methylated analogue (MePD) bind strongly to DNA by nearest-neighbour intercalation with little sequence selectivity, presenting reactive azide groups in the major groove. PD is neutral in aqueous solution but experiences binding-coupled protonation on interaction with DNA with an apparent pK a shift of 2.5 units. MePD can be click modified in situ on DNA with alkyne-functionalised thienyl-pyrrole as a precursor for conducting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 105 publications
5
23
0
Order By: Relevance
“…Conditions for full loading of the DNA are described in the Supporting Information and were designed to ensure quantitative binding of 1 or 2 (i.e., minimal unbound material) up to the intercalation saturation limit. We previously postulated that the intercalators 1 and 2 remain effectively locked into the DNA helix after click functionalization as supported by linear dichroism spectroscopy (LD) of the [DNA⊃ 2 ]+ 5 complex (see the Supporting Information) 8. In addition, LD studies also indicated that the click product [ 2 + 5 ] did not intercalate into DNA if added as a presynthesized unit, possibly due to hydrophobic and steric barriers.…”
Section: Methodsmentioning
confidence: 92%
See 3 more Smart Citations
“…Conditions for full loading of the DNA are described in the Supporting Information and were designed to ensure quantitative binding of 1 or 2 (i.e., minimal unbound material) up to the intercalation saturation limit. We previously postulated that the intercalators 1 and 2 remain effectively locked into the DNA helix after click functionalization as supported by linear dichroism spectroscopy (LD) of the [DNA⊃ 2 ]+ 5 complex (see the Supporting Information) 8. In addition, LD studies also indicated that the click product [ 2 + 5 ] did not intercalate into DNA if added as a presynthesized unit, possibly due to hydrophobic and steric barriers.…”
Section: Methodsmentioning
confidence: 92%
“…Similarly, in further non‐intercalated control experiments, the synthesis of [ 1+3 ], [ 1+4 ], [ 1+5 ], and [ 2+5 ] was clean and in all cases the products were double‐clicked (NMR and MS data, presented in the Supporting Information). Therefore, having previously reported that 1 and 2 intercalate into DNA with association constants between 10 4 –10 6 M −1 ,8 and now demonstrated that 1 and 2 undergo the click reaction at both azido sites, we reasoned that the DNA‐azido intercalator complexes, [DNA⊃ 1 ] and [DNA⊃ 2 ] are sufficiently stable to allow for “click” functionalization, that is, in situ modification.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tuite, Pike and co‐workers reported the DNA‐templated self‐assembly of multiple proflavine‐derived compounds (Figure ). Binding to DNA was shown to occur following the nearest‐neighbor intercalation, as evidenced by negative induced circular dichroism signals as well as linear dichroism, with association constants in the range 10 4 –10 6 m − 1 and little sequence selectivity . λ‐DNA was used as a template onto which up to 24251 intercalators can bind per helix.…”
Section: Dna‐templated Self‐assembly Of Small Moleculesmentioning
confidence: 99%